2020
DOI: 10.1016/j.chempr.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis, FLPs, and Beyond

Abstract: This Perspective describes the development of the field of catalysis and the advent of metal-free catalysis by focusing on the use of main-group species as frustrated Lewis pair catalysts. In addition to outlining the major advances in this area, it also discusses how these advances could evolve and affect the future of catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(80 citation statements)
references
References 77 publications
(60 reference statements)
1
79
0
Order By: Relevance
“…Interestingly, compound 3 does not react with additional H 2 O under inert atmosphere but decomposes readily in air at room temperature. Although FLPs are well known to heterolytic bond cleavages in water [36][37][38][39][40][41][42][43][44] and dihydrogen, [56][57][58][59][60][61] to the best of our knowledge, water reduction by metal-free FLP systems has never been achieved before. A control reaction of free PPh 3 and BCy 3 in 1:2 ratio at 50 °C in benzene did not yield any H 2 overnight (see spectra in SI), which means the architecture of the rigid phenylene backbone and the proximity of two boranes is essential for this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, compound 3 does not react with additional H 2 O under inert atmosphere but decomposes readily in air at room temperature. Although FLPs are well known to heterolytic bond cleavages in water [36][37][38][39][40][41][42][43][44] and dihydrogen, [56][57][58][59][60][61] to the best of our knowledge, water reduction by metal-free FLP systems has never been achieved before. A control reaction of free PPh 3 and BCy 3 in 1:2 ratio at 50 °C in benzene did not yield any H 2 overnight (see spectra in SI), which means the architecture of the rigid phenylene backbone and the proximity of two boranes is essential for this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the concept of FLPs have been largely extended, [2–3] mainly by two groups, i. e. Stephan's group focuses on the inter‐molecular FLPs [4] and Erker's group focuses on the intra‐molecular FLPs [5] . Nowadays the FLP chemistry has become one of the important research topic in the field of catalysis and has been shown many important applications, [6–8] such as capture and activation a series of small molecules, i. e. H 2 , CO 2 , SO 2 [9–11] and hydrogenation reactions, including reduction of CO 2 to chemical products, [12] and saturation of ethylene, [13] acrylic, [14] 6,6‐dimethylpentafulvene [15] and complexation of nitrous oxide [16] …”
Section: Introductionmentioning
confidence: 99%
“…The current focus of many research groups involves the development of new methodologies to make catalysis ''greener". Using earth-abundant, less toxic, firstrow transition metals, chemists are re-examining well known strategies to make them more environmentally-friendly [29][30][31]. Boron-based compounds are widely employed as main group catalysts: boronic acids prominently for the activation of hydroxy functional groups [32], doubly B-doped (hetero)arenes as activators of p-block molecules [33], and boranes capable of activating a large number of substrates via a variety of transformations (Figure 2).…”
Section: Catalysismentioning
confidence: 99%